2018
DOI: 10.3847/1538-4357/aad197
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of the Solar Cycle Over One Cycle

Abstract: The prediction of the strength of future solar cycles is of interest because of its practical significance for space weather and as a test of our theoretical understanding of the solar cycle. The Babcock-Leighton mechanism allows predictions by assimilating the observed magnetic field on the surface. Since the emergence of sunspot groups has random properties, making it impossible to accurately predict the solar cycle and strongly limiting the scope of cycle predictions, we develop a scheme to investigate the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 69 publications
5
40
0
Order By: Relevance
“…Similarly the updated SSN max for cycle 25 is 131 ± 11 if solar minimum of cycle 24 happens in 2021 suggesting also an upcoming cycle 25 stronger than cycle 24. Our prediction, in fact, agrees with the predictions made by Jiang et al (2018), Pesnell and Schatten (2018), and Petrovay et al (2018) who claimed a similar result for the amplitude of cycle 25.…”
Section: 1029/2019ja027508supporting
confidence: 92%
See 1 more Smart Citation
“…Similarly the updated SSN max for cycle 25 is 131 ± 11 if solar minimum of cycle 24 happens in 2021 suggesting also an upcoming cycle 25 stronger than cycle 24. Our prediction, in fact, agrees with the predictions made by Jiang et al (2018), Pesnell and Schatten (2018), and Petrovay et al (2018) who claimed a similar result for the amplitude of cycle 25.…”
Section: 1029/2019ja027508supporting
confidence: 92%
“…This unusual behavior has drawn the attention of researchers worldwide who have attempted to predict the amplitude of solar cycle 25 (Bhowmik & Nandy, 2018;Cameron et al, 2016;Gopalswamy et al, 2018;Hathaway & Upton, 2016;Iijima et al, 2017;Janardhan et al, 2015;Jiang et al, 2018;Kakad et al, 2017;Kirov et al, 2018;Macario-Rojas et al, 2018;Pesnell & Schatten, 2018;Petrovay et al, 2018;Sarp et al, 2018;Upton & Hathaway, 2014, 2018. The different estimates of SSN in V1.0 and V2.0 for the amplitude of cycle 25 by different researchers along with the ratio of peak SSN of cycle 25 to cycle 24 are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The period of low 365 nm albedo in this study overlaps the known maximum time of solar activity cycle (Jiang et al 2018) as shown in figure 15. This resembles the correlation of Neptune's reflectivity and the solar activity cycle (Aplin & Harrison 2016).…”
Section: Possible Causes Of the Observed Albedo Variationssupporting
confidence: 66%
“…In the simulations of this study, we excluded the active region with the sunspot group area with less than 100 msh. The tilt angle is determined following Cameron et al (2010) as in Section 3 except for using the cycle dependent factor T n to simulate multiple solar cycles (Cameron et al 2010;Jiang et al 2011Jiang et al , 2018. The separation between polarities is modeled as in Section 3.…”
Section: Effect Of Asymmetry In Whole Solar Cyclementioning
confidence: 99%